2018
DOI: 10.1016/j.ijrobp.2018.06.103
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Outcomes of NRG Oncology/RTOG 0232: A Phase III Study Comparing Combined External Beam Radiation and Transperineal Interstitial Permanent Brachytherapy with Brachytherapy Alone in Intermediate Risk Prostate Cancer

Abstract: There was some evidence of a larger deterioration in overall sexual function in the 74 Gy arm compared to both hypofractionated arms, which was most marked for sexual bother (Table). Sexual function appeared to deteriorate across all arms between 2 and 5-years. There were no significant differences in general QOL domain scores between arms at 2 and 5 years. Conclusion: Change in bowel or urinary symptoms up to 5 years was similar between the treatment schedules in the CHHiP trial, but there was evidence of les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In a subset analysis based on the Radiation Therapy Oncology Group (RTOG) 0232 trial inclusion criteria, much in accordance with our practice (Gleason score 7 vs. Gleason score < 7 and PSA 10–20 ng/ml) they demonstrated similar overall survival with the combination therapy and question the clinical importance of the small survival benefit faced with potential more side effects. The RTOG 0232 randomized trial results presented recently in ASTRO 2018 suggest similar segregation into the group of intermediate risk patients show that EBRT combined with brachytherapy is not necessary in favorable intermediate group patients [2] while ASCENDE-RT trial showed improved bPFS with brachytherapy boost given with EBRT + ADT compared to EBRT + ADT alone for intermediate and high risk disease [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subset analysis based on the Radiation Therapy Oncology Group (RTOG) 0232 trial inclusion criteria, much in accordance with our practice (Gleason score 7 vs. Gleason score < 7 and PSA 10–20 ng/ml) they demonstrated similar overall survival with the combination therapy and question the clinical importance of the small survival benefit faced with potential more side effects. The RTOG 0232 randomized trial results presented recently in ASTRO 2018 suggest similar segregation into the group of intermediate risk patients show that EBRT combined with brachytherapy is not necessary in favorable intermediate group patients [2] while ASCENDE-RT trial showed improved bPFS with brachytherapy boost given with EBRT + ADT compared to EBRT + ADT alone for intermediate and high risk disease [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore high volume and longer prospective follow up reports are welcome to substantiate this treatment modality and perhaps answer some still debated issues, such as the role of adjuvant short term androgen deprivation therapy (ADT), and of combined external beam radiotherapy (EBRT) in appropriate patients. The RTOG 0232 randomized trial aiming to answer the clinical dilemma of treating Gleason score (GS) 7 by brachytherapy or brachytherapy and EBRT has recently been published as Abstract only [2]. Many brachytherapy centers have moved towards the use of brachytherapy only, in cases with intermediate D'Amico risk group patients and do not reserve brachy-monotherapy for low risk patients only [3].…”
Section: Introductionmentioning
confidence: 99%
“…Brachytherapy boost was also associated with worse sexual function declines at 24 months. However, none of these differences met the predefined clinically significant threshold (effect sizes > = 0.5 standard deviation) ( 61 ).…”
Section: Brachytherapy Boost and Quality Of Lifementioning
confidence: 90%
“…Toxicity in both groups was limited, but there was a shift towards higher grade toxicities, as well as poorer patient-reported outcomes at 2 years in the EBRT + LDRBT arm than the LDRBT monotherapy arm. [56]. The authors conclude that men with intermediate-risk prostate cancer may safely receive brachytherapy alone.…”
Section: Evidence For Hdrbt Monotherapymentioning
confidence: 95%